Seeking normality: Parents' experiences of childhood stroke. (15th October 2018) - McKevitt, Christopher; Topor, Marta; Panton, Anna; Mallick, Andrew A.; Ganesan, Vijeya; Wraige, Elizabeth; Gordon, Anne
Abstract: Background: Incidence of paediatric stroke has been estimated to range from 1.2 to 13 per 100, 000 children under 18 years of age. It is a significant cause of long‐term morbidity in children with long‐term impacts on physical, cognitive, psychological, and social outcomes. However, little is known about the experiences of parents caring for a child with stroke. Such information is needed to inform the development of child‐ and family‐centred care. Methods: We conducted in‐depth interviews with parents of children with stroke. Participants were purposively sampled from three regional specialist services in England, based on the age of the child at stroke onset and time since first stroke. Interviews used a topic guide and were audio recorded and transcribed in full. Thematic analysis was conducted to develop an account that reflected patients' experiences from their own perspectives. Results: Twelve parents participated with five children classified as having no to mild deficits and seven with moderate to severe deficits. Parents were concerned about the effects of stroke on the child's psychological, cognitive, and social well‐being. Significant impacts on parents own well‐being and on the family were reported. Although most experienced good quality acute care, meeting the child's needs after hospital discharge was problematic, with low levels of awareness of paediatric stroke among professionals and difficulties accessing relevant information and services. Meeting special education needs was variable. Parents were proactive in seeking to establish a sense of normality for the child and themselves. Conclusions: The findings illuminate a wider picture of paediatric stroke than indicated by clinical outcomes alone. Parents' experiences varied according to the child's needs but also family's situation and geographical location. Particular attention should be paid to co‐ordinating services to meet multiple needs after discharge from hospital.